Climate Variability and Change in Central America: What Does It Mean for Water Managers? - Hidalgo, Hugo G. (Frontiers in Water, 2021)
Central America is a unique climate region, due to its location and shape, as well as the many large and local scale climate processes that influence its variability and change at a large range of spatial and time scales. Observed temperature trends have been increasing significantly and they are expected to increase even more in the future, potentially increasing aridity. Managers should make an informed decision on whether a sophisticated modeling approach is best for your region, or simpler planning approaches are available. Always ask and question the uncertainty of information that is presented. Use this modeling information as a dynamic and constantly changing effort, as future evolves new analysis would need to be performed as models and data become more accurate.